Paradoxical embolisation of a catheter fragment to a coronary artery in an infant with congenital heart disease. Issue 4 (October 1991) - Klys, H S; Salmon, A P; De Giovanni, J V
Abstract : Six weeks after cardiac catheterisation via the right femoral vein an infant underwent an anatomical correction for transposition of the great vessels and closure of a large ventricular septal defect. The patient died intraoperatively as a result of severe left ventricular dysfunction. Necropsy showed an old myocardial infarction associated with thrombosis of the circumflex coronary artery. Electron probe x ray analysis showed that foreign refractile material within the thrombus contained bismuth, an element used in the construction of some cardiac catheters. This is believed to be the first report of "paradoxical" coronary embolisation of catheter-derived material and highlights the usefulness of electron probe x ray analysis.